Avaliação do efeito precoce da orquiectomia radical unilateral no perfil de proteínas do plasma seminal de homens portadores de tumor de células germinativas de testículo - Andrade, Maria Beatriz Ribeiro De [UNIFESP] (2019)
Objective: To evaluate the effect of orchiectomy on the seminal plasma proteomic profile of men with testicular germ cell tumors. Methods: Seventeen men with Testicular Germ Cell Tumors provided one semen sample before (Pre-orchiectomy) and another 30 days after orchiectomy (Post-orchiectomy). Following liquefaction, an aliquot was used for semen analysis and other one was centrifuged for collection of seminal plasma. The remaining volume was criopreservated. The seminal plasma was used to proteomic analysis .For semen analysis a Student’s t-test for paired samples was used and to proteomic analysis a one sample Student’s t-test was performed. For both analysis was adopted p˂0,05. Effect size was assessed using Cohen’s d coefficient. Results: No significant difference was observed in semen analysis. Two hundred and seven proteins were identified and quantified with high fidelity, of which five were increase in the pre-orchiectomy period and eight proteins were increase in post-orchiectomy period. Conclusion: Removal of the affect testis alters the seminal plasma molecular environment.